Layers of meaning: elements of visual journaling - Hadar, Rakefet (Stackpole Books, 2021)
"Visual Journey Journaling is an innovative artistic language made up of seven elements: Intention, Magical Coincidence, Background, Images, Lines, Color, and Text. Visual Journey Journaling (VJJ) invites you to a fascinating world where you will reconnect with your hidden inner artist to create "soul pages" using simple techniques and subtle guidelines to take a look inside yourself. Rakefet Hadar has taught these methods for many years, guiding even inexperienced artists to find the stories within themselves"--